O Som do Spotify BR: dimensões do consumo de música digital no Brasil - Gabriel Borges Vaz de Melo (2017)
Technological innovations, commonly associated with economic development, also have a significant impact on social practices and individual behavior. Therefore, the cultural practices are inserted in the context of digitalization and modify the forms of consumption of cultural goods, altering the perception of the multiple cultural manifestations and the taste of individuals. Historically, among the cultural segments that most adapt and innovate, music plays a prominent role. In recent decades, a number of changes have been observed due to the growth of digital market, which has become even more evident with the recent rise of streaming services. This dissertation seeks to identify, seize and analyze the consumption of digital music in Brazil. The purpose is to show trends and tastes of individuals, taking into account musical genres and incorporating the notion of space and time of consumption. As for the methodology, it was used data from the Spotify streaming platform, collected through reading and collecting scripts in web domains (Spotify Charts and Every Place at Once) and information in the application programming interface (API) of the service itself. The results show that the genres sertanejo universitário and international pop have a great national reach, configuring the most consumed musical styles nowadays. However, other national genres, partly secondary or marginalized by the market and traditional media, obtain relevant and distinct demand in some Brazilian cities. Thus, there are places with specific taste for certain genres, while others, the consumption is more diversified. Amongst the contributions of this study is the evidence of a regionalization of musical taste in Brazil, which suggests potential musical niches when inserted in the context of digital market.